The making of economic society - Heilbroner, Robert L. (Englewood Cliffs, N.J. : Prentice-Hall, 1972)
This book is an attempt to present some of the basic content of economics in this mingled light of theory and history. Thus it begins with an effort to bring history home by a broadside exposure to some of the more sobering and disturbing aspects of history's cutting edge - the present
Includes bibliographical references and index.
osc 28/01/2019
Loans
Keywords: Economic history